2001
DOI: 10.1097/00130478-200110000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hypoxemia-ischemia and reoxygenation with 21% or 100% oxygen in newborn piglets: Effects on extracellular levels of excitatory amino acids and microcirculation

Abstract: Significantly higher levels of excitatory amino acids in striatum, significantly lower mean arterial pressure, and a significantly greater degree of hypoperfusion in cerebral cortex were found after reoxygenation with 21% oxygen compared with 100% oxygen in normocapnic, hypoxemic-ischemic newborn piglets. This suggests a less favorable outcome in the group receiving room air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 29 publications
1
31
2
1
Order By: Relevance
“…14,15 There is evidence in newborn animal models of asphyxia that exposure to high concentrations of oxygen at resuscitation does not confer any clinical advantage and is potentially harmful at the cellular level. 16,17 Two animal models of hypoxia-ischemia and persistent bradycardia found that those resuscitated with room air rather than 100% oxygen developed untoward biochemical changes in the brain (LOE 5 18,19 ).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…14,15 There is evidence in newborn animal models of asphyxia that exposure to high concentrations of oxygen at resuscitation does not confer any clinical advantage and is potentially harmful at the cellular level. 16,17 Two animal models of hypoxia-ischemia and persistent bradycardia found that those resuscitated with room air rather than 100% oxygen developed untoward biochemical changes in the brain (LOE 5 18,19 ).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…The amino acid content was determined by high-performance liquid chromatography (Perkin Elmer, Norwalk, Conn., USA) by a method modified from Lindroth and Mopper [10], as previously described [7]. Due to technical problems with the analyzer, amino acid measurements had to be excluded in 4 animals (2 in each group).…”
Section: Analysis Of Amino Acidsmentioning
confidence: 99%
“…Measurements of changes in cerebral cortical microcirculation were performed with a two-channel laser Doppler flowmeter (Periflux 4001 Master, Perimed AB, Stockholm, Sweden) as previously described [7].…”
Section: Laser Doppler Flowmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in other studies, the duration of postischemic reoxygenation with use of pure oxygen varies from 5 min to 24 h regardless of the resuscitation-induced changes in CBF (4,5,25). This may limit the clinical value of experimental data.…”
mentioning
confidence: 95%